Zofia Kuratowska : lekarz, polityk, dyplomata - Jaszunski, Grzegorz (Warszawa : Oficyna Wydawnicza Rytm, 2000)
The biography of Zofia Kuratowska, a noted Polish physician, politician and diplomat.
Keywords: Kuratowska, Zofia; Physicians -- Poland -- Biography; Politicians -- Poland -- Biography; Diplomats -- Poland -- Biography